The more you have, the more you lose: Muscle mass changes in trauma patients with prolonged hospitalizations. Issue 4 (April 2023) - Bradford, James M.; Cardenas, Tatiana C.P.; Lara, Sabino; Olson, Kristofor; Teixeira, Pedro G.; Aydelotte, Jayson D.; Trust, Marc D.; DuBose, Joseph; Ali, Sadia; Brown, Carlos VR
Abstract: Introduction: Sarcopenia is a clinically relevant loss of muscle mass with implications of increased morbidity and mortality in adult trauma populations. Our study aimed to evaluate loss of muscle mass change in adult trauma patients with prolonged hospital stays. Methods: Retrospective analysis using institutional trauma registry to identify all adult trauma patients with hospital length of stay >14 days admitted to our Level 1 center between 2010 and 2017. All CT images were reviewed, and cross-sectional area (cm 2 ) of the left psoas muscle was measured at the level of the third lumbar vertebral body to determine total psoas area (TPA) and Total Psoas Index (TPI) normalized for patient stature. Sarcopenia was defined as a TPI on admission below gender specific thresholds of 5.45(cm 2 /m 2 ) in men and 3.85(cm 2 /m 2 ) in women. TPA, TPI, and rates of change in TPI were then evaluated and compared between sarcopenic and non-sarcopenic adult trauma patients. Results: There were 81 adult trauma patients who met inclusion criteria. The average change in TPA was -3.8 cm 2 and TPI was -1.3 cm 2 . On admission, 23% ( n = 19) of patients were sarcopenic while 77% ( n = 62) were not. Non-sarcopenic patients had a significantly greater change in TPA (-4.9 vs. -0.31, p <0.0001), TPI (-1.7 vs. -0.13, p <0.0001), and rate of decrease in muscle mass ( p = 0.0002). 37% of patients who were admitted with normal muscle mass developed sarcopenia during admission. Older age was the only risk factor independently associated with developing sarcopenia (OR: 1.04, 95%CI 1.00–1.08, p = 0.045). Conclusion: Over a third of patients with normal muscle mass at admission subsequently developed sarcopenia with older age as the primary risk factor. Patients with normal muscle mass at admission had greater decreases in TPA and TPI, and accelerated rates of muscle mass loss compared to sarcopenic patients.